Impact of obesity on periodontal condition - a systematic review of literature - Bartosik-Zielińska, Diana; Bartosik, Magdalena; Blicharz, Monika; Blicharz, Agnieszka; Swatko, Tomasz (Journal of Education, Health and Sport, 2023)
Introduction: In recent years, more and more of the population is overweight and obese. Adipose tissue is a metabolically active tissue that releases adipocytokines and inflammatory hormones. As a result of the excess amount of adipose tissue in the body, the risk of systemic diseases as well as diseases occurring in the oral cavity, including periodontitis, increases. Aim of the study: A systematic review of the existing evidence on the association between overweight/obesity and periodontitis. Materials and methods: The literature available in the PubMed database was perfomed, using the following keywords: obesity and periodontitis; obesity; periodontal disease; overweight; periodontitis. Results: The results of the presented studies indicate a positive correlation between overweight and obesity and periodontitis. In many publications, the odds ratio for periodontitis increased with increasing BMI. In addition, a high WC rate is associated with an increased incidence of periodontitis. Pro-inflammatory mediators responsible for the development and advancement of periodontitis are produced, among others, by adipose tissue. Conclusion: An increased amount of adipose tissue as a metabolically active tissue, secreting pro-inflammatory mediators, can significantly affect the development and periodontitis. Therefore, overweight and obese people with a high BMI and WC may have a higher risk of periodontitis.